Capacity Building for Research in Critical Care: A Pilot Program in the Eastern Mediterranean Region. (8th January 2021) - Nazer, Lama H.; Kleinpell, Ruth; Olsen, Keith; Hawari, Feras
Abstract : Research productivity in the Eastern Mediterranean Region is relatively low in all fields, including critical care. We describe a capacity-building research program that was piloted with 11 clinicians from the Eastern Mediterranean Region, who had minimal research experience. The program was conducted over 1 year, with a structure that specifically addressed factors that contribute to low research productivity. We describe the structure of the program, the faculty involved, the feasibility, and challenges faced, as well as the impact of the program on research output. At a small scale, the program was generally feasible and demonstrated promising results. Evaluating the feasibility of conducting such a program over a longer period of time and with a larger group of participants is necessary since research capacity-building programs require multiple years to demonstrate a significant impact on research output.